2019
DOI: 10.15366/archaeofauna2019.28.016
|View full text |Cite
|
Sign up to set email alerts
|

Explotación de Conepatus chinga (Carnivora, Mephitidae) en la cuenca superior y media del río Limay (noroeste de la Patagonia) durante el Holoceno tardio

Abstract: RESUMEN: Se presentan los resultados del análisis tafonómico de los restos óseos y dentarios de Conepatus chinga (zorrino común) provenientes de siete sitios arqueológicos del Holoceno tardío ubicados en la cuenca superior y media del río Limay (noroeste de la Patagonia). La baja incidencia de agentes naturales postdepositacionales indicó buena conservación y rápido enterramiento de los conjuntos. Las evidencias tafonómicas revelaron que C. chinga se utilizó principalmente para el consumo de su carne y en meno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…The Bayesian mixing models present a limitation for discriminating among more than six/seven resources with different isotopic mean values when using only two biotracers (Moore & Semmens, 2008;Stock et al, 2018). Consequently, animals found in the zooarchaeological record in low frequencies, such as carnivores (puma, foxes, small cats, and ferrets), other rodent species (Lagidium, Dolichotis, Ctenomys, and cavins), birds, fish, and mollusks, cannot be incorporated into the mixing models (Andrade & Fernández, 2017;Cordero, 2010;Guillermo et al, 2019;Lezcano et al, 2010;Menegaz, 1996;Pérez & Smith, 2008;Silveira, 1996Silveira, , 1999Silveira & Cordero, 2014). The where the joint exploration of the zooarchaeological record and human isotopic values indicated that, among the resources found in low frequency, fish and birds could be important (Gord on et al, 2018), and the inclusion of these resources in the Bayesian mixing models substantially improves the results (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The Bayesian mixing models present a limitation for discriminating among more than six/seven resources with different isotopic mean values when using only two biotracers (Moore & Semmens, 2008;Stock et al, 2018). Consequently, animals found in the zooarchaeological record in low frequencies, such as carnivores (puma, foxes, small cats, and ferrets), other rodent species (Lagidium, Dolichotis, Ctenomys, and cavins), birds, fish, and mollusks, cannot be incorporated into the mixing models (Andrade & Fernández, 2017;Cordero, 2010;Guillermo et al, 2019;Lezcano et al, 2010;Menegaz, 1996;Pérez & Smith, 2008;Silveira, 1996Silveira, , 1999Silveira & Cordero, 2014). The where the joint exploration of the zooarchaeological record and human isotopic values indicated that, among the resources found in low frequency, fish and birds could be important (Gord on et al, 2018), and the inclusion of these resources in the Bayesian mixing models substantially improves the results (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…El aprovechamiento preferencial de los ítems de mayor jerarquía (como Lama guanicoe y Rhea pennata) impone una movilidad muy alta, como la que se infiere para los primeros ocupantes de Epullán Grande y para quienes dejaron los restos del Componente Traful en la cueva Traful I (Crivelli Montero et al, , 1996b. En cambio, la inclusión de una gama variada de especies animales menos rendidoras (que comprenda armadillos, zorrinos y roedores) o vegetales (e.g., cactus) requiere mayores permanencias, que se reflejan en asentamientos más estables (e.g., Ciampagna & Mange, 2017;Crivelli Montero et al, 1996bFernández, 2001;Fernández et al, 2016;Guillermo et al, 2019). La muestra faunística de CLC1 es demasiado escasa como para indicar una tendencia clara; empero, el procesamiento exhaustivo de L. guanicoe durante toda la ocupación del alero y la incorporación de R. pennata y Chaetophractus villosus en el periodo más tardío (Capa I) podría relacionarse con un proceso de intensificación en la explotación de los recursos (Guillermo et al, 2020).…”
Section: La Molienda Como Indicio De Intensificación En La Explotació...unclassified